2017
DOI: 10.1159/000452991
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Pretreatment Advanced Lung Cancer Inflammation Index (ALI) in Diffuse Large B Cell Lymphoma Patients Treated with R-CHOP Chemotherapy

Abstract: Background: The Advanced Lung Cancer Inflammation Index (ALI, body mass index × albumin/neutrophil-to-lymphocyte ratio) has been demonstrated to be a prognostic factor of survival in some solid cancers. We retrospectively investigated the usefulness of the ALI to predict chemotherapy response and survival in 212 patients with diffuse large B cell lymphoma (DLBCL) treated with R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone) chemotherapy. Methods: Patients were allocated to a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 44 publications
2
47
1
Order By: Relevance
“…In theory, these easily measureable, cheap, and broadly available blood-borne surrogates are useful for predicting the clinical outcome in many if not all types of cancer patients. In this issue of Acta Haematologica , Park et al [2] report clinical evidence for the prognostic use of the Advanced Lung Cancer Inflammation Index (ALI) in diffuse large B-cell lymphoma (DLBCL) patients. Within the limitations of a retrospective observational cohort study, these investigators demonstrated a consistent association between a low ALI and poor outcomes in 212 patients with DLBCL undergoing standard R-CHOP immune chemotherapy.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In theory, these easily measureable, cheap, and broadly available blood-borne surrogates are useful for predicting the clinical outcome in many if not all types of cancer patients. In this issue of Acta Haematologica , Park et al [2] report clinical evidence for the prognostic use of the Advanced Lung Cancer Inflammation Index (ALI) in diffuse large B-cell lymphoma (DLBCL) patients. Within the limitations of a retrospective observational cohort study, these investigators demonstrated a consistent association between a low ALI and poor outcomes in 212 patients with DLBCL undergoing standard R-CHOP immune chemotherapy.…”
mentioning
confidence: 99%
“…In their study on DLBCL, Park et al [2] defined a cut-off value for low ALI, thereby dichotomizing their patient population into a “low ALI” subgroup comprising roughly a third of their population and a subpopulation above this cut-off. Importantly, the probabilities of complete remission after R-CHOP, 5-year progression-free survival, and 5-year overall survival were around 20% lower in this “low ALI” group as compared to the patients above the ALI cut-off, respectively.…”
mentioning
confidence: 99%
See 3 more Smart Citations